The Psychological Dynamics of Youth with Internet Addiction - Maghfiroh, Virgin Suciyanti; Muqoddam, Faqihul (TAZKIYA Journal of Psychology, 2020)
Internet users are increasing over time. The increasing of internet users, especially for youth people, tends to create internet addiction in each user. Internet addiction in youth people is interesting to know their attitudes and behavior psychologically, because it is related to their daily conditions. This research was conducted to answer the psychological dynamics of youth people with internet addiction. To answer that, there are some research questions such as what factors make young people addicted to the internet? what do they feel when not using the internet? and what are the impacts of using the internet for them? The research method uses qualitative methods with narrative descriptive approaches. Data analysis using thematic data analysis. The results showed that 1) the need for affiliation, high curiosity about information, and online business became the reason youth people access the internet, 2) youth people feel anxious and loneliness when not accessing the internet, 3) the impact of accessing the internet such as sad and happy on their emotions that occur according to situations and conditions. In addition, researchers also found interesting things from their attitude who experienced boredom when often using the internet but failed for them to stop or reduce access to the internet. The conclusion that the internet now is a necessary for youth people, because the internet has a major impact on their psychological factors.